Ab Initio Molecular Dynamics with Explicit Solvent Reveals a Two‐Step Pathway in the Frustrated Lewis Pair Reaction. Issue 49 (3rd November 2015) - Pu, Maoping; Privalov, Timofei
Abstract: The role solvent plays in reactions involving frustrated Lewis pairs (FLPs)—for example, the stoichiometric mixture of a bulky Lewis acid and a bulky Lewis base—still remains largely unexplored at the molecular level. For a reaction of the phosphorus/boron FLP and dissolved CO2 gas, first principles (Born–Oppenheimer) molecular dynamics with explicit solvent reveals a hitherto unknown two‐step reaction pathway—one that complements the concerted (one‐step) mechanism known from the minimum‐energy‐path calculations. The rationalization of the discovered reaction pathway—that is, the stepwise formation of PC and OB bonds—is that the environment (typical organic solvents) stabilizes an intermediate which results from nucleophilic attack of the phosphorus Lewis base on CO2 . This finding is significant because presently the concerted reaction‐path paradigm predominates in the rationalization of FLP reactivity. Herein we point out how to attain experimental proof of our results. Abstract : A two‐step pathway : For a bulky Lewis base and a bulky Lewis acid reacting with CO2, state‐of‐the‐art molecular modelling reveals a hitherto unknown two‐step reaction path because the environment (solvent) stabilizes the Lewis base plus CO2 short‐range association. Previous theoretical considerations in the gas phase have pointed out only the concerted (one‐step) reaction pathway.